2020
DOI: 10.3390/nano10122426
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Magnetic Hyperthermia Properties of Pristine and Mildly Reduced Graphene Oxide/Magnetite Nanocomposite Dispersions

Abstract: We present a study on the magnetic hyperthermia properties of graphene oxide/magnetite (GO/MNP) nanocomposites to investigate their heat production behavior upon the modification of the oxidation degree of the carbonaceous host. Avoiding the harsh chemical conditions of the regular in situ co-precipitation-based routes, the oppositely charged MNPs and GO nanosheets were combined by the heterocoagulation process at pH ~ 5.5, which is a mild way to synthesize composite nanostructures at room temperature. Nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Research has found that magnetic hyperthermia is a novel procedure that offers a safe, powerful, and simple treatment method to meet these complicated challenges [92][93][94][95][96]. In this procedure, which has recently seen rapid development, magnetic nanomaterials can be used to improve hyperthermia efficiency compared to traditional hyperthermia methods for the erosion of tumors [97][98][99][100][101][102][103][104][105][106].…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%
“…Research has found that magnetic hyperthermia is a novel procedure that offers a safe, powerful, and simple treatment method to meet these complicated challenges [92][93][94][95][96]. In this procedure, which has recently seen rapid development, magnetic nanomaterials can be used to improve hyperthermia efficiency compared to traditional hyperthermia methods for the erosion of tumors [97][98][99][100][101][102][103][104][105][106].…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%
“…At the same time, it could take part in the formation of a polyimide chain during in situ polymerization, leading to even better compatibility of NH 2 -GO in the polyimide matrix. To remove most of the oxygen-containing groups of GO and regain its electrical conductivity, l -ascorbic acid (LAA), an effective and eco-friendly reducing agent, was applied to perform chemical reduction on NH 2 -GO nanosheets. Amino-functionalized chemically reduced graphene oxide/polyimide (NH 2 -CRG/PI) composite materials were then fabricated through a typical in situ polymerization process.…”
Section: Introductionmentioning
confidence: 99%